Analysis of the current state of the compositional ensemble of Yerevan’s central square: challenges and proposed solutions - Sagaryan, Zhora; Azatyan, Karen (Budownictwo i Architektura / Civil and Architectural Engineering, 2025)
This article explores contemporary challenges related to the spatial environment of public squares, focusing specifically on the architectural ensemble of Yerevan’s Republic Square. It assesses the square’s current state by highlighting critical issues and synthesising approaches developed across various stages of its development. The methodology combines archival research, on-site surveys, and comparative evaluation of historical and recent proposals. The study identifies the square’s principal spatial, circulation, and aesthetic problems, analyses their underlying causes, impacts, and risks, and compares them with the solutions previously advanced. Findings reveal that many long-recognised issues remain unaddressed because the project still lacks a clearly formulated set of objectives to guide coordinated redevelopment. Accordingly, the article formulates a hierarchy of priorities and outlines strategic directions for implementation. These recommendations provide a workable framework for multi-level planning in Republic Square and the adjacent “Small Centre” area, while contributing to the broader discourse on designing and managing architectural ensembles of public squares.